Marine Square, Port of Spain Trinidad, B.W.I. - (:unkn) unknown (My University, 2010)
A view of Marine Square, located in downtown Port of Spain, which was renamed Independence Square in 1962. Postcard number 28.
Colour: Coloured (hues of green and orange); Style: Landscape; Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Plazas--Trinidad and Tobago; Buildings--Trinidad and Tobago; Trees--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--Port of Spain; Promenades (Pedestrian areas)--Trinidad and Tobago; Pedestrian areas--Trinidad and Tobago; Marine Square (Port of Spain); Independence Square (Port of Spain)